2008
DOI: 10.1007/s10995-008-0353-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Centering Pregnancy to Traditional Care in Hispanic Mothers

Abstract: This study provides information regarding Hispanic mothers' responses to an alternative care delivery model. Preliminary evidence suggests CPM compares with traditional care and yields a high degree of patient satisfaction. Specific pregnancy-related knowledge deficits were identified in both groups that could focus prenatal education. In light of similar outcomes in both groups; patient and provider satisfaction and economics would therefore be a factor when choosing a model of prenatal care delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 20 publications
2
90
2
Order By: Relevance
“…For example, Robertson and colleagues 14 demonstrated the benefits of group prenatal visits in previous work with Latinas. Given the importance of culturally and linguistically sensitive care, 24 government interest in reducing health disparities, 25 and previous work suggesting that minority populations with limited English proficiency and different cultural beliefs benefit from programs tailored to their needs for optimal pregnancy care, 26 -28 expanding group prenatal visits is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Robertson and colleagues 14 demonstrated the benefits of group prenatal visits in previous work with Latinas. Given the importance of culturally and linguistically sensitive care, 24 government interest in reducing health disparities, 25 and previous work suggesting that minority populations with limited English proficiency and different cultural beliefs benefit from programs tailored to their needs for optimal pregnancy care, 26 -28 expanding group prenatal visits is needed.…”
Section: Discussionmentioning
confidence: 99%
“…10 This model has been adapted successfully for use with African American teenagers, women in the military, and Latinas. [11][12][13][14] Barr et al 15 published the only known empirical article on group prenatal care by family physicians; they reported that women who attended group visits experienced fewer cesarean deliveries and less preterm labor compared with women receiving traditional prenatal care.…”
mentioning
confidence: 99%
“…The gFNP curriculum is based on FNP materials, adapted for delivery in a group, and the FNs provide routine midwifery care in pregnancy and routine infant health checks. Reflecting 'Centering Pregnancy' (Robertson et al, 2009) mothers are encouraged to conduct some of the necessary pregnancy and child development checks themselves. Based on pilot work and to distinguish recipients of gFNP from those eligible for FNP, eligibility for gFNP and for the trial was: expectant mothers aged <20 with one or more previous live births or aged 20-24 with low/no educational qualifications and no previous live births.…”
Section: The Gfnp Programmementioning
confidence: 99%
“…The CenteringPregnancy model has also been found to improve women's use of family planning services (Hale et al, 2014), increase breast feeding rates (Grady and Bloom, 2004;Ickovics et al, 2007;Klima et al, 2009;TannerSmith, Steinka-Fry, and Lipsey, 2013), and reduce biological, behavioral, and psychosocial risks for HIV when HIV self-management was integrated into the model (Kershaw et al, 2009). One qualitative study of African-American and Hispanic women who were on Medicaid or uninsured found that the women were enthusiastic about a group approach to antenatal care (Novick et al, 2011); other studies have documented high levels of patient satisfaction with the CenteringPregnancy model compared with the traditional individual model of antenatal care (Grady and Bloom, 2004;Ickovics et al, 2007;Klima et al, 2009;Robertson, Aycock, and Darnell, 2009), and one study from the Netherlands documented an increase in interpersonal trusting relationships for women in the program leading to increased self-confidence (Kweekel et al, 2016).…”
Section: Case Study 1: Sharon Rising and Centeringpregnancy Model Ovementioning
confidence: 99%